Preparation method of alkali-activated phosphate tailing-based geopolymer grouting material
By using water glass and sodium hydroxide exciters in phosphorus tailing base excitation polymers, phosphorus tailings participate in the reaction and improve compressive strength, solving the problems of insufficient compressive strength and high processing complexity in the prior art. , realizes efficient and low-cost utilization of phosphorus tailings resources.
Patent Information
- Application Number
- CN202411622722.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-31
AI Technical Summary
The existing phosphorus tailing base-activated geological polymers have insufficient compressive strength, complex processing technology and high cost, making it difficult to meet the needs of high-strength application scenarios.
Phosphorus tailings, blast furnace slag powder, polycarboxylic acid water reducer and sand as raw materials, and water glass and sodium hydroxide as excitants, so as to improve the participation and pressure resistance of phosphorus tailings through de-dolescence and ionic cross-linking reactions. Strength, simplify process and reduce costs.
It realizes high compressive strength phosphorus tailings base-exciting polymer, which is simple in process and low in cost, meets higher strength application needs, and reduces the environmental impact of phosphorus tailings and blast furnace slag.
Smart Images

Figure CN119219378A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a geopolymer grouting material, in particular to a method for preparing an alkali-activated phosphorus tailings-based geopolymer grouting material. Background Art
[0002] Phosphate tailings are solid wastes generated during the mining and beneficiation of phosphate ore. They are low-grade phosphate ore. A large amount of surplus phosphate tailings accumulate in tailings ponds and farmland, which not only occupies a large amount of land resources, but also leads to the waste of mineral resources and causes serious pollution to the environment. Among them, the main mineral components of phosphate tailings are dolomite, and there are also a small amount of fluoroapatite and quartz. They are secondary resources rich in calcium and magnesium, and have huge development space in many aspects of the chemical industry.
[0003] Blast furnace slag is a solid waste and a byproduct of iron smelting plants. Currently, only a small amount of blast furnace slag is used to produce building materials, and its huge stockpile poses a potential threat to the environment and life safety. Blast furnace slag is rich in active substances. If it is fully utilized, it can better solve the problem of blast furnace slag storage and realize resource recycling.
[0004] At present, the application of phosphate tailings is mainly used as filling materials, phosphorus recovery from phosphate tailings, fertilizer production and cementitious materials. Portland cement is an important building cementitious material with large application volume and wide application. Therefore, replacing part of Portland cement with phosphate tailings is considered to be one of the most promising ways to utilize phosphate tailings resources.
[0005] Alkali-activated geopolymer is an environmentally friendly green solidification technology for solid waste, and is also a new type of cementitious material that replaces ordinary silicate cement, with better gelling properties, including alkali-activated phosphate tailings-based polymer. For example, an article titled "Preparation and Interface State Study of Phosphorus Tailings-Based Geopolymer" reported in the Journal of Central South University publicly reported an alkali-activated phosphate tailings-based polymer, the preparation method of which is phosphate tailings as the main raw material, fly ash as the activator, and water glass as the alkaline activator. Under the conditions of phosphate tailings and fly ash solid content of 60% and 40% respectively, and water-cement ratio of 0.22, a high-performance geopolymer with a compressive strength of 38.8MPa was prepared.
[0006] However, the inventors of the present application further discovered that in the phosphorus tailings-fly ash system, since fly ash is a low-calcium waste residue, fly ash slowly dissolves under the stimulation of water glass, and thus a small amount of zeolite structure and C-(a)-sh gel and N-(a)-sh are formed, and these substances wrap a large amount of phosphorus tailings that do not react with the alkaline activator solution, thereby obtaining the phosphorus tailings-based alkali-activated geopolymer. It can be seen that in the phosphorus tailings-fly ash system, the phosphorus tailings mainly play a filling role and do not participate in the reaction during the reaction process. Therefore, the compressive strength of the entire geopolymer is not very high, only 38.8MPa.
[0007] In addition, patent document CN115849782A discloses a preparation method of alkali-activated geopolymer cemented ultrafine phosphate tailings filling material, the method is to dry the phosphate tailings and carbide slag in a 60°C oven for 12 hours, grind to 200 mesh after cooling, under the condition that the mass ratio of water to solid waste is 0.35-0.60, ultrafine phosphate tailings, slag are raw materials, alkali activator is carbide slag (Ca, Al, Si, etc.), sodium sulfate (sodium sulfate), sodium hydroxide and industrial waste alkali water mixed composite alkali activator, mixed reaction synthesizes geopolymer. And the mortar is cured in an oven at 60°C for 6 hours, then continued to be cured at room temperature for 7 days, and then demoulding. In the method, the phosphate tailings and carbide slag need to be dried and ground, the process is cumbersome and increases the cost; the mortar not only needs to be heated but also needs to be cured for 7 days, the slurry molding time is slow, the strength is low, and the 7d maximum strength is 11.7Mpa. In addition, the complex composition of the composite activator is easy to produce more by-products.
[0008] Therefore, how to further improve the compressive strength of phosphate tailings-based polymers so that they can meet application scenarios with higher strength requirements, while reducing their processing costs and simplifying the processing technology, is still the goal of researchers in this field. Summary of the invention
[0009] In order to solve the above technical problems, the present invention provides a method for preparing an alkali-activated phosphorus tailings-based polymer grouting material. The present invention has the characteristics of simple process, low processing cost, and high compressive strength of the obtained phosphorus tailings-based polymer.
[0010] The technical solution of the present invention:
[0011] The invention discloses a method for preparing an alkali-activated phosphorus tailings-based polymer grouting material, which is prepared by taking phosphorus tailings, blast furnace slag powder, polycarboxylic acid water reducer and sand as raw materials and taking water glass and sodium hydroxide as activators.
[0012] Preferably, the preparation method of the aforementioned alkali-activated phosphorus tailings-based polymer grouting material comprises the following steps:
[0013] S1. Weigh phosphate tailings, blast furnace slag powder, sand, polycarboxylate water reducer, water glass, sodium hydroxide and water;
[0014] S2. Evenly mix the phosphorus tailings, blast furnace slag powder, sand and water, and then continue to add polycarboxylic acid water reducer, water glass and sodium hydroxide, and stir evenly to obtain the phosphorus tailings base polymer grouting material.
[0015] Preferably, the preparation method of the aforementioned alkali-activated phosphate tailings-based polymer grouting material comprises, by weight, 400-600 parts of phosphate tailings, 400-600 parts of blast furnace slag powder, 1400-1600 parts of sand, 150-250 parts of water glass and 50-60 parts of sodium hydroxide; the water-to-solid ratio of the total amount of the phosphate tailings and blast furnace slag powder to water is 0.35-0.45; the addition amount of the polycarboxylate water reducer is 0.2-0.4% of the total amount of the phosphate tailings and blast furnace slag.
[0016] Preferably, the preparation method of the aforementioned alkali-activated phosphate tailings-based polymer grouting material comprises, by weight, 450-550 parts of phosphate tailings, 450-550 parts of blast furnace slag powder, 1450-1550 parts of sand, 170-220 parts of water glass and 52-55 parts of sodium hydroxide; the water-to-solid ratio of the total amount of the phosphate tailings and blast furnace slag powder to water is 0.38-0.42; the addition amount of the polycarboxylic acid water reducer is 0.25-0.35% of the total amount of the phosphate tailings and blast furnace slag.
[0017] Preferably, the preparation method of the alkali-activated phosphorus tailings-based polymer grouting material comprises, by weight, 500 parts of phosphorus tailings, 500 parts of blast furnace slag powder, 1500 parts of sand, 200 parts of water glass and 60 parts of sodium hydroxide; the water-to-solid ratio of the total amount of the phosphorus tailings and blast furnace slag powder to water is 0.4; the addition amount of the polycarboxylate water reducer is 0.3% of the total amount of the phosphorus tailings and blast furnace slag
[0018] Preferably, in the aforementioned method for preparing alkali-activated phosphorus tailings-based polymer grouting material, the phosphorus tailings are reverse flotation phosphorus tailings with a water content of 5-15% and a median particle size of 45-50 μm.
[0019] Preferably, in the aforementioned method for preparing alkali-activated phosphate tailings-based polymer grouting material, the CaO content of the phosphate tailings is 55-60%.
[0020] Preferably, in the aforementioned method for preparing alkali-activated phosphate tailings-based polymer grouting material, the median particle size of the blast furnace slag powder is 10-12 μm.
[0021] Preferably, in the aforementioned method for preparing alkali-activated phosphorus tailings-based polymer grouting material, the total content of CaO, Al2O3 and SiO2 in the blast furnace slag powder is 80-90%.
[0022] Preferably, in the aforementioned method for preparing alkali-activated phosphate tailings-based polymer grouting material, the sand is machine-made sand with a particle size of 2-3 mm.
[0023] In the phosphorus tailings-blast furnace slag system of the present invention, dolomite, the main component of the phosphorus tailings, undergoes two chemical reactions, namely, dedolomization and ion crosslinking, as shown in the following:
[0024] De-dolomitization reaction equation:
[0025] CaMg(CO3)2+2NaOH=CaCO3↓+Mg(OH)2+2H2O (1)
[0026] The chemical reaction equation of ionic crosslinking reaction is:
[0027] CaCO3+2NaOH+H4SiO4=CaH2SiO4+Na2CO3+2H2O (2)
[0028] (Ca,Mg)CO3+2NaOH+H4SiO4=(Ca,Mg)H2SiO4+Na2CO3+2H2O (3)
[0029] Beneficial effects of the present invention:
[0030] 1. The phosphate tailings-based polymer of the present invention does not need to be heated during processing, and has a small number of activators and a low price. Therefore, it has the advantages of simple processing technology and low cost.
[0031] 2. In the phosphorus tailings-blast furnace slag system of the present invention, by using water glass and sodium hydroxide as a composite activator, the dissolution of dolomite and aluminosilicate in the geopolymer raw materials can be promoted, and the calcium ions and magnesium ions dissolved from the dolomite can react quickly with the aluminosilicate gel to accelerate the rate of the geopolymer reaction. Since the phosphorus tailings actually participate in the reaction, the phosphorus tailings of the present invention are not used as a filling material, and its compressive strength is higher. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Attached Figure 1 The XRD diagram of the geopolymer prepared by mixing the phosphate tailings and the high slag in a ratio of 1:1 according to the present invention;
[0033] Attached Figure 2 This is an XPS graph of the geopolymer obtained when the phosphorus tailings and high slag are mixed in a ratio of 1:1 according to the present invention;
[0034] Attached Figure 3 This is a 14d SEM image of the geopolymer prepared by the present invention with a ratio of 50% phosphate tailings and 50% high slag;
[0035] Attached Figure 4The Mg, Ca, Al, and O element mapping diagram of the geopolymer prepared by the present invention with a ratio of 50% phosphate tailings and 50% high slag at 14d;
[0036] Attached Figure 5 The 28d SEM image of the geopolymer prepared by the present invention with a ratio of 30% phosphate tailings and 70% high slag;
[0037] Attached Figure 6 The 28d EDS graph of the geopolymer prepared by the present invention with a ratio of 30% phosphate tailings and 70% high slag;
[0038] Attached Figure 7 The 28d SEM image of the geopolymer prepared by the present invention with a ratio of 50% phosphate tailings and 50% high slag;
[0039] Attached Figure 8 The 28d EDS graph of the geopolymer prepared by the present invention with a ratio of 50% phosphate tailings and 50% high slag;
[0040] from Figure 1 It can be seen that with the extension of hydration time, calcium carbonate and magnesium in the phosphate tailings are gradually consumed, and the intensity of the diffraction peak is significantly weakened. Figure 2 A new peak appeared at 2θ=29.3° in XRD, indicating that calcium silicate hydrate (CSH) or calcium aluminum silicate hydrate (CASH) gel structure was formed during the alkali excitation process, and peaks of magnesium silicate hydrate (MSH) appeared at 2θ=35° and 60°.
[0041] from Figure 2 It can be seen that with the increase of solidification time, the binding energy of Mg1s in the 50% phosphate tailings + 50% slag system began to gradually decrease, reaching 1299.05 eV at 28 days. In the process of preparing geopolymers, the structure of magnesium in the phosphate tailings changed and a new gel MSH was formed.
[0042] right Figure 3 and Figure 7 By comparison, it can be clearly seen that under the stimulation of water glass and sodium hydroxide composite alkali, a lot of gel products emerge on the surface. As the hydration time continues, the originally smooth surface of the phosphate tailings suffers serious damage, and at the same time, a large amount of gel products flourish on its surface. Figure 8 as well as Figure 4 The Mg, Ca, Al, and O element mapping diagrams are analyzed in depth. 2+ It has a strong polarization effect, which reduces the degree of polymerization of NASH gel and transforms it into CASH gel with lower degree of polymerization. 2+ and Ca 2+Will be with [SiO4] 4- 、[AlO4] 5- The tetrahedrons combine with each other to form MSH, CSH, and CASH gels, which is highly consistent with the results of XRD and XPS analysis.
[0043] In addition, compared Figure 5 and Figure 7 Further analysis shows that the more the amount of phosphate tailings is added, the more its morphology is destroyed. The reason is that a larger calcium content will increase the lattice spacing of some facets in the dolomite crystal structure. These lattice defects will accelerate the erosion of water glass on dolomite, which also strongly proves that increasing the amount of phosphate tailings can activate the activity of phosphate tailings and make it participate in geopolymer reaction in large quantities. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.
[0045] Embodiments of the present invention
[0046] Example 1
[0047] A method for preparing an alkali-activated phosphorus tailings-based polymer grouting material comprises the following steps:
[0048] S1. Weigh 500g of phosphate tailings, 500g of blast furnace slag powder, 1500g of sand, 3g of polycarboxylate water reducer, 200g of water glass and 60g of sodium hydroxide, and weigh the corresponding water according to the total solid amount of phosphate tailings and blast furnace slag powder at a water-solid ratio of 0.4;
[0049] S2. Evenly mix the phosphorus tailings, blast furnace slag powder, sand and water, and then continue to add polycarboxylic acid water reducer, water glass and sodium hydroxide, and stir evenly to obtain the phosphorus tailings base polymer grouting material.
[0050] Example 2
[0051] A method for preparing an alkali-activated phosphorus tailings-based polymer grouting material comprises the following steps:
[0052] S1. Weigh 400g of phosphate tailings, 600g of blast furnace slag powder, 1400g of sand, 2g of polycarboxylate water reducer, 150g of water glass and 50g of sodium hydroxide, and weigh the corresponding water according to the total solid amount of phosphate tailings and blast furnace slag powder at a water-solid ratio of 0.35;
[0053] S2. Evenly mix the phosphorus tailings, blast furnace slag powder, sand and water, and then continue to add polycarboxylic acid water reducer, water glass and sodium hydroxide, and stir evenly to obtain the phosphorus tailings base polymer grouting material.
[0054] Example 3
[0055] A method for preparing an alkali-activated phosphorus tailings-based polymer grouting material comprises the following steps:
[0056] S1. Weigh 600g of phosphate tailings, 400g of blast furnace slag powder, 1600g of sand, 4g of polycarboxylate water reducer, 250g of water glass and 54g of sodium hydroxide, and weigh the corresponding water according to the total solid amount of phosphate tailings and blast furnace slag powder at a water-solid ratio of 0.45;
[0057] S2. Evenly mix the phosphorus tailings, blast furnace slag powder, sand and water, and then continue to add polycarboxylic acid water reducer, water glass and sodium hydroxide, and stir evenly to obtain the phosphorus tailings base polymer grouting material.
[0058] Example 4
[0059] A method for preparing an alkali-activated phosphorus tailings-based polymer grouting material comprises the following steps:
[0060] S1. Weigh 450g of phosphate tailings, 550g of blast furnace slag powder, 1450g of sand, 2g of polycarboxylate water reducer, 170g of water glass and 52g of sodium hydroxide, and weigh the corresponding water according to the total solid amount of phosphate tailings and blast furnace slag powder at a water-solid ratio of 0.38;
[0061] S2. Evenly mix the phosphorus tailings, blast furnace slag powder, sand and water, and then continue to add polycarboxylic acid water reducer, water glass and sodium hydroxide, and stir evenly to obtain the phosphorus tailings base polymer grouting material.
[0062] Example 5
[0063] A method for preparing an alkali-activated phosphorus tailings-based polymer grouting material comprises the following steps:
[0064] S1. Weigh 550g of phosphate tailings, 450g of blast furnace slag powder, 1550g of sand, 4g of polycarboxylate water reducer, 220g of water glass and 58g of sodium hydroxide, and weigh the corresponding water according to the total solid amount of phosphate tailings and blast furnace slag powder at a water-solid ratio of 0.42;
[0065] S2. Evenly mix the phosphorus tailings, blast furnace slag powder, sand and water, and then continue to add polycarboxylic acid water reducer, water glass and sodium hydroxide, and stir evenly to obtain the phosphorus tailings base polymer grouting material.
[0066] Experimental example
[0067] According to the process steps of Example 1, the phosphate tailings and slag are proportioned in mass ratios of 1:9, 3:7, 5:5 and 7:3, respectively, and are recorded as groups 1, 2, 3 and 4, respectively, and 20wt% of water glass, 6wt% of sodium hydroxide, 0.3wt% of polycarboxylate water reducer and 150wt% of sand are added to the 4 groups of materials, respectively, and water is added at a water-solid ratio of 0.4 to mix and stir evenly, and then poured into molds respectively, and demolded after curing for 1d under the conditions of 20°C and humidity of 95%, and then the respective costs and compressive strengths are calculated and measured. The results are shown in Table 1:
[0068]
[0069] In Table 1, the compressive strength of the phosphorus tailings-slag binary system at different ages was tested. Within the 28d age, the compressive strength of the 30% phosphorus tailings + 70% slag system was very close to that of the 10% phosphorus tailings + 90% slag, and the compressive strength of the 30% phosphorus tailings + 70% slag system was very close to that of the 50% phosphorus tailings + 50% slag system as the gap shortened over time. The 50% phosphorus tailings + 50% slag system developed slowly in the early stage of alkali excitation, but in the later stage of alkali excitation, its compressive strength was very close to that of the 30% phosphorus tailings + 70% slag system. Therefore, when the phosphorus tailings content does not exceed 50%, as the content increases, the phosphorus tailings mainly affect the development of early strength, but the long-term strength loss is not large. In addition, with the increase in the content of phosphorus tailings, the fluidity of the mortar increases.
[0070] Reaction mechanism: In the phosphorus tailings-slag cementitious material system, slag, as a highly active volcanic ash material, reacts early to form a large amount of C-(a)-sh gel, which mainly provides silicon-aluminum components. Water glass and sodium hydroxide are mainly used as alkaline activators, providing an alkaline environment for the activation reaction while also providing a large amount of silicon elements. The crystalline phase in the slag component has low activity and plays a major role in the later strength of the cementitious material after the alkali-dolomite reaction. The slag is composed of a large amount of irregular glass and is mainly divided into two parts. One part is a continuous phase mainly composed of Ca, which occupies most of the volume of the glass phase. The other part is a discontinuous phase mainly composed of silicon, that is, a "silicon-rich phase", which is tightly wrapped by a "calcium-rich phase". These two phases constitute the unique glass structure of slag. The water glass and sodium hydroxide composite activator can provide strong alkalinity and soluble silicate ions. In a strong alkaline environment, the silicon oxygen protective layer on the slag surface is destroyed, resulting in the rupture of Si-O-Si, Si-O-Al, and Al-O-Al bonds, releasing some Mg 2+ and Ca 2+ . In a strong alkaline environment, the SL structure continues to deteriorate, leaching [SiO4] 4- 、[AlO4] 5-The tetrahedrons enter the solution and recombine to form CSH and CASH gels. As the reaction time increases, the dolomite in PTS reacts with alkali to generate Ca 2+ Mg 2+ It will react with the hydration products of water glass to generate silicate products such as hydrated calcium magnesium silicate gel, thereby improving the compressive strength of later samples.
[0071] In summary, the solution of the present invention not only greatly reduces the impact of flotation phosphate tailings and slag on the environment, but also improves the utilization value of phosphate tailings in construction.
[0072] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an alkali-activated phosphorus tailings-based polymer grouting material, characterized in that: It is made from phosphate tailings, blast furnace slag powder, polycarboxylate water reducer and sand as raw materials, and water glass and sodium hydroxide as activators.
2. The method for preparing the alkali-activated phosphorus tailings-based polymer grouting material according to claim 1, characterized in that: The steps include: S1. Weigh phosphate tailings, blast furnace slag powder, sand, polycarboxylate water reducer, water glass, sodium hydroxide and water; S2. Evenly mix the phosphorus tailings, blast furnace slag powder, sand and water, and then continue to add polycarboxylic acid water reducer, water glass and sodium hydroxide, and stir evenly to obtain the phosphorus tailings base polymer grouting material.
3. The method for preparing the alkali-activated phosphorus tailings-based polymer grouting material according to claim 2, characterized in that: Calculated by weight, it includes 400-600 parts of phosphate tailings, 400-600 parts of blast furnace slag powder, 1400-1600 parts of sand, 150-250 parts of water glass and 50-60 parts of sodium hydroxide; the water-to-solid ratio of the total amount of the phosphate tailings and blast furnace slag powder to water is 0.35-0.45; the added amount of the polycarboxylate water reducer is 0.2-0.4% of the total amount of the phosphate tailings and blast furnace slag.
4. The method for preparing the alkali-activated phosphorus tailings-based polymer grouting material according to claim 3, characterized in that: Calculated by weight, it includes 450-550 parts of phosphate tailings, 450-550 parts of blast furnace slag powder, 1450-1550 parts of sand, 170-220 parts of water glass and 52-55 parts of sodium hydroxide; the water-solid ratio of the total amount of the phosphate tailings and blast furnace slag powder to water is 0.38-0.42; the added amount of the polycarboxylate water reducer is 0.25-0.35% of the total amount of the phosphate tailings and blast furnace slag.
5. The method for preparing the alkali-activated phosphorus tailings-based polymer grouting material according to claim 4, characterized in that: Calculated by weight, it includes 500 parts of phosphate tailings, 500 parts of blast furnace slag powder, 1500 parts of sand, 200 parts of water glass and 54 parts of sodium hydroxide; the water-to-solid ratio of the total amount of the phosphate tailings and blast furnace slag powder to water is 0.4; the added amount of the polycarboxylate water reducer is 0.3% of the total amount of the phosphate tailings and blast furnace slag.
6. The method for preparing the alkali-activated phosphorus tailings-based polymer grouting material according to claim 1 or 2, characterized in that: The phosphate tailings are reverse flotation phosphate tailings with a water content of 5-15% and a median particle size of 45-50 μm.
7. The method for preparing the alkali-activated phosphorus tailings-based polymer grouting material according to claim 1 or 2, characterized in that: The CaO content of the phosphate tailings is 55-60%.
8. The method for preparing the alkali-activated phosphorus tailings-based polymer grouting material according to claim 1 or 2, characterized in that: The median particle size of the blast furnace slag powder is 10-12 μm.
9. The method for preparing the alkali-activated phosphorus tailings-based polymer grouting material according to claim 1 or 2, characterized in that: The total content of CaO, Al2O3 and SiO2 in the blast furnace slag powder is 80-90%.
10. The method for preparing the alkali-activated phosphorus tailings-based polymer grouting material according to claim 1 or 2, characterized in that: The sand is machine-made sand with a particle size of 2-3 mm.
